Synthesis, Identification and evaluation of antibacterial activity of some new substituted N-benzyl-5-Bromo Isatin - Al-Adhami, Huda J.A; Al-Majidi, Suaad M.H. (Iraqi Journal of Science, 2023)
This research includes synthesis of new heterocyclic derivatives of N-benzyl-5-bromoisatin. New 1, 2, 4-triazole, oxazoline and thiazoline derivatives of [N-benzyl-5-bromo-3-(Ethyliminoacetate)-indole-2-one] (2) have been synthesized. The preparation process started by the reaction of 5-bromoisatin with sodium hydride in dimethylformamide (DMF) at 0°C, gave suspension of sodium salt of 5-bromoisatin and subsequent reaction with benzylchloride to give N-benzyl-5-bromoisatin (1). Compound (1) reacted with ethylglycinate (Schiff base) obtained the intermediate compound (2) which reacted with different reagents in two ways. The first way, compound (2) reacted with (hydrazine hydrate, semicarbazide, phenylsemicarbazide and thiosemicarbazide), then converted to (hydrazide, semicarbazide, phenylsemicarbazide and thiosemicarbazide) derivatives respectively to give compounds (3-6). After that compounds (4-6) cyclized in presence of alkaline media (4N-NaOH) to form substituted 1, 2, 4-triazole derivatives (7-9). In alkaline media (20%KOH) compound (3) reacted with CS2 to give potassium salt (10) that reacted with excess of hydrazine hydrate to give compound (11). The second way includes reaction of compound (3) with (phenylisocyanate and phenylisothiocyanate) to give compound (5 and 12), which undergo cyclization with p-bromophenacylbromide to obtain oxazoline (13) and thiazoline (14). Newly synthesized compounds were identified via spectral methods; their [FTIR and some of them by 1HNMR, 13C-NMR] and measurements of some of its physical properties and also some specific reactions. Furthermore the effects of the synthesized compounds were studied on some strains of bacteria.